Low genetic and high environmental diversity at adaptive traits in Pinus pinea from provenance tests in France and Spain - Mutke S.; Gordo J.; Khouja M.L.; Fady B. (Mediterranean stone pine for agroforestry, 2013)
Mediterranean Stone pine (Pinus pinea L.) is a native species of the Mediterranean region, widely used for reforestation. It is characterised by a low genetic variation both at phenotypic traits and molecular markers. In the early nineties, experimental plots were established in several countries bordering the Mediterranean Sea for studying the distribution of genetic variability among provenances in adaptative traits as survival, vegetative and reproductive phase change, phenology and growth. Here we report results of the first decade at seven trial sites in France and Spain. The survival, ontogeny and growth patterns were homogeneous among provenances but differed among sites. On the other hand, the phenotypic plasticity of the species and its sensitivity to microsite (soil) variation produced strong spatial autocorrelations of the response variables, both between and within sites, which masked greatly the variation between provenances. Nearest-neighbours adjustments that captured the spatial pattern at each site reduced the error term and increased the significance of the geographic genetic variation considerably. Comparison of the adjusted average heights of each provenance showed a common trend between sites, with a lightly more vigorous growth in plants from colder or inland provenances. These results confirm the conclusions obtained in earlier analyses of the Spanish test sites, where these provenances showed also an earlier spring shoot phenology and a stronger tendency to polycyclism.
AGROPINE 2011 International Meeting on Mediterranean Stone Pine for Agroforestery, 2011/11/17-19, Valladolid (Spain)